The influence of the creative problem solving (CPS) model on increasing the mathematics procedural ability of class VII students on whole numbers - Dewi, Triana; Rosmaiyadi, Rosmaiyadi; Husna, Nurul (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2023)
This research aims; (1) to describe the difference in increasing students' mathematical procedural abilities between those using the Creative Problem Solving (CPS) learning model and the direct learning model on integer material; (2) to describe the influence of the CPS on students' mathematical procedural abilities on integer material; (3) to describe students' high motivation to learn through the CPS on integer material. This type of research is a Quasi-Experimental Design with research design The Non-equivalent Posttest Only Control Group Design. Samples were taken by the saturated sampling technique. The sample consists of two classes, namely class VIIA as the control class and class VIIB as the experimental class. Based on the analysis results, it is concluded that; (1) there is a difference in improvement between the experimental class and the control class. The T-Two Independent Samples test evidences this, it is found that there are differences in the mathematical improvement of the experimental class students and the control class students; (2) the influence of the CPS model on students' mathematical procedural abilities. The value of Effect Size is 6.0 which is in the significant criteria; (3) students' learning motivation taught by the CPS is high.